Deficyty emocjonalne młodych dorosłych wychowanków rodzin zastępczych - Jasielska , Aleksandra; Buchnat Marzena, Marzena (Studia Edukacyjne, 2018)
The study was aimed to determine the role of attachment bond in emotional functioning in alexithy-mia and emotional processing in foster care alumni. The participants with experience of personal rejection – adult foster care alumni during the transition from foster care to adulthood (N = 29) and persons without such experience (N = 32) took part in the study. The Experiences in Close Relation-ships Scale, Toronto Alexithymia Scale and Emotional Processing Scale were used. Results present that insecure pattern of attachment occurs with alexithymia in ineffective emotional processing. We confront the results with the construct of emotion representations as the key to comprehend observed deficits in emotional functioning.